2017
DOI: 10.1111/pin.12571
|View full text |Cite
|
Sign up to set email alerts
|

Skene's gland adenocarcinoma with intestinal differentiation: A case report and literature review

Abstract: Adenocarcinoma of Skene's gland (the female homolog to the male prostate) is extremely rare, with only a few cases reported. We present a case of Skene's gland adenocarcinoma with intestinal differentiation. The patient was a 69-year-old Japanese woman who was operated on for a recurrent tumor of the external ostium of the urethra. Histopathologically, the tumor showed glandular and cribriform patterns with a signet-ring cell component in a mucus lake. Immunohistochemically, the tumor cells were positive for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…[14][15][16] It is interesting to point out that our third case expressed PAP, and that the columnar component of both tumors expressed racemase. Muto et al 15 and Kato et al 17 both presented a case with mucinous features that expressed PAP and PSA, respectively. It was suggested in accordance to these findings that columnar/mucinous adenocarcinoma could arise from periurethral glands.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] It is interesting to point out that our third case expressed PAP, and that the columnar component of both tumors expressed racemase. Muto et al 15 and Kato et al 17 both presented a case with mucinous features that expressed PAP and PSA, respectively. It was suggested in accordance to these findings that columnar/mucinous adenocarcinoma could arise from periurethral glands.…”
Section: Discussionmentioning
confidence: 99%
“…In males, the prostate has an important secretory function in the reproductive tract; particularly in humans, there is great concern related to the incidence of benign (Langan, 2019) and malign hyperplasia (Chang et al, 2014) in adults. In women, however, concern regarding hyperplastic alterations in this gland is more recent (Muto et al, 2017). The initial development of this organ takes place during the prenatal period and in rodents it has been shown to be susceptible to environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The female prostate stroma was more proliferative following exposure to finasteride, but differences were not observed in the epithelium or stroma of the male prostate. This sex‐specific variation indicates complex effects of finasteride on the female prostate, along with changes in smooth muscle formation that may indicate that the female prostate can be affected at low doses of finasteride, which becomes worrisome in the face of the presence of prostate glands in a proportion of women and the possibility that they may be affected by similar diseases to those which occur in the male prostate, such as cancer and prostatitis . In addition, there is evidence in the gerbil that the female prostate may also suffer from increased susceptibility to pathological conditions due to exposure to exogenous hormones and/or endocrine regulators during prostate development, which increases concerns that exposure to certain substances, such as finasteride, even at low dosages such as the one used in this study, may act to generate neglected changes in prostate development and increases in susceptibility to diseases associated with aging, since safety parameters have been determined for the male prostate.…”
Section: Discussionmentioning
confidence: 99%
“…This type of investigation becomes relevant in the light of the presence of functional prostates in at least half of women, which are unencapsulated, much smaller than the male prostate, approximately 5 g in weight, and can spread into the urethra especially in a more medial region . Evidence has accumulated that the female prostate could be affected by similar pathologies to those that occur in the male, such as adenocarcinomas and prostatitis . In addition, there are studies that have indicated that the female prostate is also impacted differently to the male's by intrauterine exposure to endocrine disrupters, in addition to exogenous hormones, and have suggested that these exposures could lead to an increased susceptibility to pathological conditions associated with aging in a sex‐specific manner .…”
Section: Introductionmentioning
confidence: 99%